On Generalized Statistical Convergence of Order ? of Difference Sequences - Et, Mikail; Altinok, Hifsi; Altin, Yavuz (Hindawi Ltd, 2013)
We introduce the concept of statistical convergence of order alpha of difference sequences, and we give some relations between the set of statistical convergence of order alpha of difference sequences and strong w(lambda)(alpha)(Delta(m), p)-summability of order alpha. Furthermore some relations between the spaces w(lambda)(alpha)(Delta(m), (p), M) and S-lambda(alpha)(Delta(m)) are examined.
Keywords: Spaces; Lambda